Religion within reason - Cahn, Steven M. (Columbia University Press, 2017)
In the views of most believers and critics, religion is essentially connected to the existence of a supernatural deity. If supernaturalism is not reasonable, the argument goes, religion cannot be reasonable-or if supernaturalism is reasonable, religion must be as well. Are faith and reason, religion and science, doomed to a constant struggle for the heart of humanity? Steven M. Cahn believes that they are not, that even if God exists, religion may not be justified and that even if religion is justified, belief in God may not be. Cahn argues that the common understanding of the relationship between religion and supernaturalism is flawed and that while supernaturalism is not reasonable, religious commitment may well be. Writing not as a theist but as one who finds much to admire in a religious life, he examines faith and reason, miracles, heaven and hell, religious diversity, and the problem of evil, using a variety of examples taken from religious thought, literature, and popular culture. Lucidly written in a nonpolemical spirit, Religion Within Reason offers an exciting new approach to the reconciliation of science and religion.